Parts of the Whole: Only Connect - Dorothy Wallace (Numeracy, 2014)
This is the first of several columns that will focus on the mechanisms by which new ideas become accepted by a culture, offering some familiar examples, deriving basic principles from these examples, and applying them to the problem of promoting quantitative literacy in an educational system. In this essay we describe how new concepts become embedded in a culture through their connections to existing ideas, and use this principle to suggest strategies of discourse about numeracy that promote it among various constituencies in the culture.